2016
DOI: 10.1371/journal.pone.0168363
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TGF-β Receptor-2 Expression and Signaling through Inhibition of Na/K-ATPase

Abstract: Transforming growth factor-beta (TGF-β) is a multi-functional cytokine implicated in the control of cell growth and differentiation. TGF-β signals through a complex of TGF-β receptors 1 and 2 (TGFβR1 and TGFβR2) that phosphorylate and activate Smad2/3 transcription factors driving transcription of the Smad-target genes. The Na+/K+-ATPase is an integral plasma membrane protein critical for maintaining the electro-chemical gradient of Na+ and K+ in the cell. We found that inhibition of the Na+/K+ ATPase by ouaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…A number of important studies have shown the role of NKA inhibition and elevation of the [Na + ]i/[K + ]i ratio in the activation of Src-EGFR-MAPK- and Akt-mediated signaling pathways triggered by CTS, and readers are referred to a recent review which more thoroughly addresses this topic [ 83 ]. The importance of this concept is highlighted by recent data showing that NKA inhibition by CTS triggers TGFβ-induced fibrosis in cultured human lung fibroblasts via [Na + ]i/[K + ]i-mediated signaling which results in augmented expression of COX-2 [ 84 ] and downregulation of TGFβ2R [ 85 ]. Cumulatively, these studies have broadened the understanding of the role of CTS signaling through the NKA in human disease.…”
Section: Cts (Cardiotonic Steroids) Nka and Fibrosismentioning
confidence: 99%
“…A number of important studies have shown the role of NKA inhibition and elevation of the [Na + ]i/[K + ]i ratio in the activation of Src-EGFR-MAPK- and Akt-mediated signaling pathways triggered by CTS, and readers are referred to a recent review which more thoroughly addresses this topic [ 83 ]. The importance of this concept is highlighted by recent data showing that NKA inhibition by CTS triggers TGFβ-induced fibrosis in cultured human lung fibroblasts via [Na + ]i/[K + ]i-mediated signaling which results in augmented expression of COX-2 [ 84 ] and downregulation of TGFβ2R [ 85 ]. Cumulatively, these studies have broadened the understanding of the role of CTS signaling through the NKA in human disease.…”
Section: Cts (Cardiotonic Steroids) Nka and Fibrosismentioning
confidence: 99%
“…increasing collagen production. Collagen protein deposition increases the extracellular matrix network [1][2][3]. The highly conserved ATP-dependent chaperone heat shock protein 90 (Hsp90) has been described as a component of the TGFβ signaling cascade [4][5][6][7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Importantly, the action of ouabain was absent in p85-KO mice, thus suggesting that side-by-side with the positive inotropic effect, the treatment with Digitalis prevents pathological cardiac hypertrophy and heart failure through activation of PI3KIA [ 167 ]. Our recent study demonstrated that anti-fibrotic action of cardiac glycosides documented by the suppression of myofibroblast differentiation in TGF-β-treated human lung fibroblasts is mediated by dissipation of transmembrane gradients of monovalent cations [ 138 , 168 ]. To the best of our knowledge, the role of Na + ,K + -ATPase inhibition and the elevated [Na + ] i /K + ] i ratio in PI3K/Akt-mediated signaling triggered by CTS has not been explored yet.…”
Section: Search For Na + I K mentioning
confidence: 99%